Membentuk Karakter Melalui Pendidikan Berbasis Nilai - Yusuf, Muhammad (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
This article explores some evidences on unsatisfactory educational achievement. It particularly is focused on its failure in forming good character for society. This fact shows the proven that there is a â€œcrucialâ€ gap between the objectives of National education and the education result which has been gained. Al-Quran pays attention toward education which oriented to character building and understanding of plenary values. Character building according to Al-Quran should be started from â€˜the innerâ€™ of man. The values is internalized and done to be custom to form good character. Al-Quran shows some examples by asking the man to experience the objects and take lesson from them in Islam terms â€œibrahâ€ from good models which full of plenary values and is hoped to form the man who have good attitude, large knowledge, good faith and religion.